Comparison of dietary quality (Healthy Eating Index-2010) according to metabolic health status in obesity: a cross-sectional study - Açık, Murat; Çakıroğlu, Funda Pınar (Progress in Nutrition, 2019)
Objectives: The aim of the study is to compare dietary quality between metabolically healthy obese (MHO) and unhealthy obese (MUO) individuals. Methods: This study was conducted with 67 MHO and 70 MUO participants who consulted the obesity clinic of Adıyaman’s Community Health Centre. Data for the study were collected via questionnaire forms by face-to-face interview. The questionnaire form includes socio-demographic characteristics, anthropometric measurements, certain biochemical findings, and dietary intake record with the 24-hour recall method.Results: The mean age of the MHO and MUO participants are 39.2±8.7 and 46.5±10.1, respectively. The mean healthy eating index-2010 (HEI-2010) scores of the MHO and MUO participants are 49.0±10.4 and 47.3±8.4, respectively (p>0.05). In addition, the scores on “dairy”, “empty calories” and “refined grains” were found to be higher in the MHO participants when compared to their counterparts and the difference between the scores is statistically significant (p<0.05). Although higher score of HEI-2010 was not associated with metabolic health among the obese subjects (OR 1.55, 95% CI 0.68-3.53, p=0.204), high dairy and low refined grains intake was associated with metabolic health (OR 2.98, 95% CI 0.57-3.06, p=0.035; OR 3.23, 95% CI 1.27-8.21, p=0.014, respectively).Conclusions: It is considered that increasing consumption of dairy products and reducing the intakes of refined grains may provide a protective effect in terms of cardiometabolic risk factors. However, there needs to conduct longitudinal follow-up cohort and clinical studies to investigate the efficacy of nutrients and food groups on cardiometabolic health despite increased fat mass.